Three-stage pH-switchable organic chromophores with large nonlinear optical responses and switching contrasts. Issue 56 (27th June 2018) - van Bezouw, Stein; Koo, Min-Jeong; Lee, Seung-Chul; Lee, Seung-Heon; Campo, Jochen; Kwon, O-Pil; Wenseleers, Wim
Abstract : First three-stage pH-switchable second-order nonlinear optical chromophores are synthesized and characterized by tunable-wavelength (non)linear spectroscopy, showing remarkably different on–off sequences. Abstract : Three-stage pH-switchable organic second-order nonlinear optical (SO NLO) chromophores are synthesized and characterized by wavelength-dependent linear and nonlinear spectroscopy. The chromophores exhibit huge SO NLO responses in their "on" stages, and large switching contrasts between adjacent stages in both SO NLO response and fluorescence quantum yield, with moreover different "on/off" sequences for closely related compounds.